2023
DOI: 10.1051/0004-6361/202245724
|View full text |Cite
|
Sign up to set email alerts
|

Massive galaxy formation caught in action at z ∼ 5 with JWST

Abstract: We report the discovery of a compact group of galaxies, CGG-z5, at z ∼ 5.2 in the EGS field covered by the JWST/CEERS survey. CGG-z5 was selected as the highest overdensity of galaxies at z > 2 in recent JWST public surveys and it consists of six candidate members lying within a projected area of 1.5 ′′ × 3 ′′ (10×20 kpc 2 ). All group members are HST/F435W and HST/F606W dropouts while securely detected in the JWST/NIRCam bands, yielding a narrow range of robust photometric redshifts 5.0 < z < 5.3. The most ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 99 publications
1
6
0
Order By: Relevance
“…Five galaxies are spectroscopically confirmed at z = 5.220-5.222 within a separation of 2″ (∼12 proper kpc, hereafter pkpc), making it the most overdense region of z > 5 galaxies in the joint footprint of JADES and FRESCO in the GOODS-N field. Similar compact assemblies of z  5 galaxies have been reported in recent JWST/NIRCam studies (Helton et al 2023;Jin et al 2023), which are suggested as the progenitors of massive galaxies (stellar mass M star  10 11 M e ) seen at lower redshifts. The two galaxies to the northwest of the bright central galaxy are blended in ground-based images obtained with the SHARDS survey (SHARDS20013448; Pérez- González et al 2013;Arrabal Haro et al 2018), which were later spectroscopically confirmed at z = 5.224 through the detection of Lyα emission (Calvi et al 2021).…”
Section: The Environment Of Hdf8501supporting
confidence: 83%
“…Five galaxies are spectroscopically confirmed at z = 5.220-5.222 within a separation of 2″ (∼12 proper kpc, hereafter pkpc), making it the most overdense region of z > 5 galaxies in the joint footprint of JADES and FRESCO in the GOODS-N field. Similar compact assemblies of z  5 galaxies have been reported in recent JWST/NIRCam studies (Helton et al 2023;Jin et al 2023), which are suggested as the progenitors of massive galaxies (stellar mass M star  10 11 M e ) seen at lower redshifts. The two galaxies to the northwest of the bright central galaxy are blended in ground-based images obtained with the SHARDS survey (SHARDS20013448; Pérez- González et al 2013;Arrabal Haro et al 2018), which were later spectroscopically confirmed at z = 5.224 through the detection of Lyα emission (Calvi et al 2021).…”
Section: The Environment Of Hdf8501supporting
confidence: 83%
“…We extract the sources by using a detection image combined from all noise weighted "wide" (W) NIRCam Long Wavelength (LW) filters available, this includes F277W, F356W, and F444W. A similar detection method for JWST data was employed in Jin et al (2023). For source extraction and the segmentation map, we used SEP (Barbary 2016), a PYTHON version of SEXTRACTOR (Bertin & Arnouts 1996).…”
Section: Source Extractionmentioning
confidence: 99%
“…At higher redshift, galaxies are less massive and more compact given the mass-size relation (e.g., see van der Wel et al 2014). Therefore, we scale the intrinsic SED accounting for multiple effects: (1) surface brightness dimming with (1 + z) 4 ; (2) using the merger trees in Jin et al (2023), we assumed that the galaxy has log (M * /M e ) = 10.8 at z = 4 and log (M * /M e ) = 10 at z = 6; (3) adopting the stellar mass-size relation at different redshift from Costantin et al (2022) for simulated 3 < z < 6 galaxies in JWST F356W image, i.e., r eff ∝ (1 + z) −0.14 ; (4) accounting for the physical scale to angular scale scaling at the assumed redshift. In order to consistently compare to the depths of JWST surveys.…”
Section: Detectability At Higher Zmentioning
confidence: 99%
“…Our work suggests this core-scale quenching has already occurred at z > 4 by gas consumption due to the starburst and/or AGN feedback. Furthermore, recent JWST observations confirm compact galaxy groups at 5 < z < 8 (e.g., Hashimoto et al 2023;Helton et al 2024;Jin et al 2023;Morishita et al 2023;Sun et al 2024). Member galaxies are mostly low-mass SFGs, but Helton et al (2024) show that more massive galaxies with larger SFR populate the overdensity region compared to the field.…”
Section: Possible Formation Scenarios Of the Qgmentioning
confidence: 96%